2020
DOI: 10.1002/chem.202002119
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Conformational Dynamics of a DNA Hairpin by α‐Synuclein in the Presence of Aqueous Two‐Phase Systems

Abstract: The effect of an amyloidogenic intrinsically disordered protein, α‐synuclein, which is associated with Parkinson's disease (PD), on the conformational dynamics of a DNA hairpin (DNA‐HP) was studied by employing the single‐molecule Förster resonance energy transfer method. The open‐to‐closed conformational equilibrium of the DNA‐HP is drastically affected by binding of monomeric α‐synuclein to the loop region of the DNA‐HP. Formation of a protein‐bound intermediate conformation is fostered in the presence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…NMR spectroscopy demonstrates that the same N-terminal domain that binds curved, negatively charged phospholipid membranes mediates aSyn’s binding to the phosphate backbone of DNA ( 7 ). Single-molecule techniques have shown that aSyn binding can stretch DNA and increase its stiffness ( 51 , 52 ), while fluorescence resonance energy transfer (FRET) assays developed to study noncanonical DNA structures show that aSyn stabilizes intermediate states on the pathway to DNA hairpin formation ( 53 ) and can bind to i-motifs ( 54 ). Although this work has started to reveal the mechanism of aSyn binding to DNA, important questions remain, including the role of potential disease-relevant aSyn posttranslational modifications in this process.…”
mentioning
confidence: 99%
“…NMR spectroscopy demonstrates that the same N-terminal domain that binds curved, negatively charged phospholipid membranes mediates aSyn’s binding to the phosphate backbone of DNA ( 7 ). Single-molecule techniques have shown that aSyn binding can stretch DNA and increase its stiffness ( 51 , 52 ), while fluorescence resonance energy transfer (FRET) assays developed to study noncanonical DNA structures show that aSyn stabilizes intermediate states on the pathway to DNA hairpin formation ( 53 ) and can bind to i-motifs ( 54 ). Although this work has started to reveal the mechanism of aSyn binding to DNA, important questions remain, including the role of potential disease-relevant aSyn posttranslational modifications in this process.…”
mentioning
confidence: 99%
“…In a recent study, Mukherjee et al. investigated the conformational dynamics of the RG‐1 G4 affected by the various external conditions such as salt concentration, co‐solutes, crowders and intrinsically disordered peptides (IDPs) [96] . Particularly they focused on α‐synuclein and the human islet amyloid polypeptide, which are involved in Parkinson's disease (PD) and type‐II diabetes mellitus, respectively.…”
Section: Introductionmentioning
confidence: 99%